Legal Strategies in Household Waste Management in Villages - Martitah, Martitah; Sulistianingsih, Dewi; Sumarto, Slamet; Prasetyo Adhi, Yuli (The Indonesian Journal of International Clinical Legal Education, 2024)
This article aims to describe and analyze legal strategies in overcoming waste management problems in villages. Rapid population growth in Kebumen Regency, especially Tanuharjo Village, Alian District, Kebumen Regency. Followed by an increase in various economic and social activities of the community which then gave rise to problems in the community. This condition is exacerbated by limited resources from local governments to deal with these problems. In general, this condition is a challenge for the village government to create an environment that can support the lives of all its citizens. Another problem that arises because of the rapid increase in the number of city residents is the increasing volume of waste. The amount or volume of waste is directly proportional to the level of public consumption of goods or materials used daily. Likewise, the type of waste depends on the type of material that the community consumes. Therefore, waste management cannot be separated from the lifestyle of the community, for this reason it must be immediately handled for the alleviation of settlements and slums in Kebumen Regency, especially in Tanuharjo Village, Alian District. The right legal strategy to overcome the waste problem in the village is through making village regulations and supported by existing village facilities.